Pengaruh Digital terhadap Minat Masyarakat di Perkotaan tentang Rumah Bergaya Arsitektur Modern Minimalis - Siti Arum Isnawati; Mikdad Tauhid (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2025)
Technology is developing very quickly, this makes it easier for people to get information through various media platforms. Architects use these technological developments to simplify and promote their work and educate the public. This article aims to find out how digital influence can influence urban people's interest in modern minimalist architectural style housing. The research data collection method uses library research and the data analysis method used is qualitative. Based on the results of this research, it can be concluded that architects use digital technology as a tool to simplify, speed up and showcase their work. Residences with a modern minimalist architectural style have become very popular and are in great demand by urban communities because their shape optimizes function and is considered to suit their lifestyle.